Effect of Retreofitting on High Performance Geo Polymer Concrete Filled Aluminium Tubular Section Using Glass Fibre Wrapping - Nachiar S, Sindhu; S, Muthukumar; S, Anandh (International Journal of Engineering and Technology, 2018)
Concrete filled tubular columns play an important role in the construction industry due to its structural behavior and earthquake resistant properties. In this paper the behavior of circular concrete filled aluminium tubular column with glass fibre wrapping is studied experimentally. High performance geo polymer concrete is used for the study. A total of twenty one specimens with 300mm height and 100mm diameter are casted and subjected to axial load. A portion of the columns were wrapped with glass fibre of different layers(single and double) with varying spacings (25mm,46.7mm and 90mm). The retrofitted effect between various layers with respect to wrapping spacings are compared.The stiffness of the columns are also found analytically using the ANSYS software.Â Â